2011
DOI: 10.1111/j.1551-2916.2011.04877.x
|View full text |Cite
|
Sign up to set email alerts
|

(1 − x)Ba(Zr0.2Ti0.8)O3x(Ba0.7Ca0.3)TiO3 Ferroelectric Thin Films Prepared from Chemical Solutions

Abstract: Using chemical solution approach on Pt/Ti/SiO2/Si substrates (1 − x)Ba(Zr0.2Ti0.8)O3–x(Ba0.7Ca0.3)TiO3 (BZT–BCT) ferroelectric thin films were prepared for the first time. Dense and crack‐free films with perovskite structure were obtained from appropriately produced precursor solution through a multiple spin‐coating process in which the individual layers were pyrolyzed at different temperatures. The effects of composition and annealing temperature on the resulting structure and properties were examined. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…In 1931, Von Gaertner et al described the structure of the ideal oxide pyrochlores. The overall formula of pyrochlore is A 2 B 2 O 7 , and it is often written as A 2 6 ] octahedral sharing all vertices to form large cavities [8]. The present study gives the impact of niobium substitution for antimony in Bi 1 [10] showed that antimony exhibit a 5+ oxidation valence.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In 1931, Von Gaertner et al described the structure of the ideal oxide pyrochlores. The overall formula of pyrochlore is A 2 B 2 O 7 , and it is often written as A 2 6 ] octahedral sharing all vertices to form large cavities [8]. The present study gives the impact of niobium substitution for antimony in Bi 1 [10] showed that antimony exhibit a 5+ oxidation valence.…”
Section: Introductionmentioning
confidence: 93%
“…These include dielectric, ferroelectric, piezoelectric, ferromagnetic, anti-ferromagnetic materials, temperature-stable high-permittivity properties, catalytic behavior, colossal magnetoresistance and host matrix for nuclear waste materials [1][2][3][4][5][6][7]. In 1931, Von Gaertner et al described the structure of the ideal oxide pyrochlores.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are processing and technique dependent and may lead to diverse properties of the thin films. Kang et al [11] found the best ferroelectric characteristic lied at x = 0.45 with a remnant polarization P r of 15.8 C/cm 2 in CSD-produced BZT-xBCT thin films while P r reached 22.15 C/cm 2 when x = 0.5 with spin-coating approach [12]. Lin et al [13] employed sol-gel method and the largest tunability up to 65% at 400 kV/cm at 100 kHz was achieved in BZT-0.55BCT film.…”
Section: Introductionmentioning
confidence: 98%
“…Various techniques such as chemical solution deposition (CSD), RF magnetron sputtering, pulsed laser deposition (PLD) etc. were employed to achieve high quality BZT-xBCT thin films [11][12][13][14][15][16]. However, due to the lack of composition-dependence study in BZT-xBCT thin film, the optimal composition in thin film form and the origins of their excellent piezoelectric properties still remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bi 2 O 3 -ZnO-Nb 2 O 5 (BZN) dielectric ceramics have received more and more attractions due to their excellent dielectric properties [9][10][11][12][13][14][15]. There are two major structural phases in this system: a cubic pyrochlore based on the Bi 1.5 ZnNb 1.5 O 7 composition and a lower symmetry monoclinic pyrochlore based on the Bi 2 (Zn 1/3 Nb 2/3 ) 2 O 7 composition.…”
Section: Introductionmentioning
confidence: 99%